ADMET Prediction of the Dominant Compound from Mangosteen (Garcinia mangostana L.) using pkCSM: A Computational Approach - Muslikh, Faisal Akhmal; Kurniawati, Evi; Ma'arif, Burhan; Zenmas, Syendriva Zeptyan; Salmasfattah, Novyananda; Dhafin, Anis Akhwan; Prasetyawan, Fendy (PT FORMOSA CENDEKIA GLOBAL, 2023)
Mangosteen (Garcinia mangostana L.) is a plant belonging to the Guttiferae family with origins in Southeast Asia. The primary components in mangosteen peel consist of xanthones, particularly α-mangostin, which displays diverse pharmacological effects such as anti-diabetic properties, antioxidant activity, and anti-inflammatory effects. However, due to the insufficient information regarding studies on pharmacokinetics (administration, distribution, metabolism, excretion, and toxicity), the objective of this investigation is to explore pharmacokinetic predictions utilizing the pkCSM web tool. The α-mangostin compound, acquired from PubChem accessible at https://pubchem.ncbi.nlm.nih.gov/, underwent pharmacokinetic analysis using the web tool available at https://biosig.lab.uq.edu.au/pkcsm/prediction. The study findings revealed that the α-mangostin compound, subjected to pharmacokinetic analysis with pkCSM, exhibited limited distribution capability.